Product Quality, Price and Digital Marketing on the Purchase Decision of Yamaha N-Max Motorcycle Users - Pandy Putra (www.amertainstitute.com, 2023)
Based on the research that has been done, the purpose of this study is to find out how much influence product quality, price, and digital marketing have on purchasing decisions for Yamaha n-max motorcycles in the community South Sulawesi, either partially or partially. simultaneously. The data analysis method used is data description, quantitative data analysis, validity test, reliability test, multiple linear regression, partial test, simultaneous test and coefficient of determination to find out the hypothesis in this study. The results of this study indicate that product quality has a partially significant effect on purchasing decisions for Yamaha n-max motorbikes in the people of the city of South Sulawesi (2.684 > 2.028). Price has a partially significant effect on purchasing decisions for Yamaha n-max motorbikes in the people of the city of South Sulawesi (3.076 > 2.028). Digital marketing has a partially significant effect on the decision to purchase a Yamaha N-Max motorbike urban residents of South Sulawesi (2,622 > 2,028). Product quality, price, and digital marketing have a significant simultaneous effect on purchasing decisions for Yamaha n-max motorbikes for the people of South Sulawesi (25.326 > 2.866). The R squared or R squared value obtained is 0.679, which means product quality, price, and digital marketing affect the decision to purchase a Yamaha n-max motorcycle. The people of South Sulawesi have an influence of 67.9% while the remaining 32.1% is influenced by other variables. which were not examined in this study such as place, brand image, promotion and so on.